An Analysis of English Language Acquitition By Trader in Kuta Beach : An Ethnography Approach - Eva; Diha, Hamjah; Putraidi, Karyawan (REFORM : Jurnal Pendidikan, Sosial, dan Budaya, 2023)
In the era of globalization and technological progress will certainly encourage qualified the human resources, have the competitiveness that will be able to enter in various fields of business, business or other work that one of them is the field of tourism. In this study, the writer use the type of qualitative research with the approach ethnography. According to Arif (2013). That Ethnography is one of many approaches in qualitative research. In Greek terms, ethnos, meaning society, race or a cultural group, ethnography means a science that explains the way people live. Technique of colectin data they are observations, Interview, Documentations, and The Voice Recorder. Techniques of Analysis Data they are Data Collection (Data Collection), Data Reduction, Display Data, and Conclusion and Verification (Conclusion: Drawing / verifying). Based on the results of data analysis conducted by researcher, research on the process of acquiring a second language on existing traders in coastal areas Kuta. Researcher can conclude that the second language acquisition on the beach traders Kuta is through several processes, namely: traders who have a formal education base in obtaining a second language, such as Following Course Institution, high school and second language that can be through lectures. and traders who do not have a formal school education background get a second language through Listening, Remembering and Imitating, and experience directly (interact)